Repurposing anthelmintic agents to eradicate resistant leukemia - Mezzatesta, Caterina; Abduli, Liridon; Guinot, Anna; Eckert, Cornelia; Schewe, Denis; Zaliova, Marketa; Vinti, Luciana; Marovca, Blerim; Tsai, Yi-Chien; Jenni, Silvia; Aguade-Gorgorio, Julia; von Stackelberg, Arend; et al. (Blood cancer journal, 2020)
Despite rapid progress in genomic profiling in acute lymphoblastic leukemia (ALL), identification of actionable targets and prediction of response to drugs remains challenging. To identify specific vulnerabilities in ALL, we performed a drug screen using primary human ALL samples cultured in a model of the bone marrow microenvironment combined with high content image analysis. Among the 2487 FDA-approved compounds tested, anthelmintic agents of the class of macrocyclic lactones exhibited potent anti-leukemia activity, similar to the already known anti-leukemia agents currently used in induction chemotherapy. Ex vivo validation in 55 primary ALL samples of both precursor B cell and T-ALL including refractory relapse cases confirmed strong anti-leukemia activity with IC50 values in the low micromolar range. Anthelmintic agents increased intracellular chloride levels in primary leukemia cells, inducing mitochondrial outer membrane depolarization and cell death. Supporting the notion that simultaneously targeting cell death machineries at different angles may enhance the cell death response, combination of anthelmintic agents with the BCL-2 antagonist navitoclax or with the chemotherapeutic agent dexamethasone showed synergistic activity in primary ALL. These data reveal anti-leukemia activity of anthelmintic agents and support exploiting drug repurposing strategies to identify so far unrecognized anti-cancer agents with potential to eradicate even refractory leukemia.
Keywords: Animals; Drug Resistance, Neoplasm; apoptóza; akutní lymfatická leukemie; Anthelmintics; myši SCID; Apoptosis; nádorové mikroprostředí; lidé; Antineoplastic Agents; protinádorové látky; chemorezistence; nádorové buňky kultivované; Mice, SCID; Tumor Cells, Cultured; Drug Repositioning; anthelmintika; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Tumor Microenvironment; zvířata; přehodnocení terapeutických indikací léčivého přípravku; Humans